2013
DOI: 10.4314/ajtcam.v11i1.25
|View full text |Cite
|
Sign up to set email alerts
|

Study on the anti-cerebral ischemia effect of borneol and its mechanism

Abstract: Background: Borneol is the processed item from resin of Dryobalanops aromatica Gaertn. f. It can enhance the activity of antioxidant enzymes in brain tissue and reduce inflammatory response by improving the energy metabolism of ischemic brain regions, and thereby reduces brain tissue damage. The objective of this paper was to study the anti-cerebral ischemia effect of borneol and its mechanism. Materials and Methods:The anti-cerebral ischemia effect of borneol was studied by ligation of bilateral common caroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 2 publications
1
15
0
Order By: Relevance
“…The increase of the expression of ICAM-1 and the opening of the BBB in our experiment are in accordance with Kong’s study in which the reduction of ICAM-1 decreased the opening of the BBB. 22 Taken together, our findings demonstrated that borneol can open the BBB and might be related with the increased expression of ICAM-1. The mechanism of how ICAM-1 opens the BBB needs to be further verified and will be our next study.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…The increase of the expression of ICAM-1 and the opening of the BBB in our experiment are in accordance with Kong’s study in which the reduction of ICAM-1 decreased the opening of the BBB. 22 Taken together, our findings demonstrated that borneol can open the BBB and might be related with the increased expression of ICAM-1. The mechanism of how ICAM-1 opens the BBB needs to be further verified and will be our next study.…”
Section: Discussionsupporting
confidence: 60%
“…A number of free radicals and cytotoxins are released when leukocytes adhere to the vascular endothelium, following endothelial cell damage and BBB opening. 22 Yun’s study showed that bloodletting puncture treatment could reduce water content of brain and the permeability of the BBB caused by ischemic stroke through the model of permanent middle cerebral artery occlusion. It was demonstrated that the expression levels of ICAM-1 and VEGF were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al, , reported that borneol enhanced blood-brain barrier permeability, improving the delivery of drugs to the brain, which is extremely interesting for association with drugs that act on the central nervous system (CNS). Moreover, Kong et al, (Kong et al, 2014), examined the effects of borneol on intracerebral inflammatory response after focal ischemia reperfusion in rats. The administration of 1-3 mg/kg (i.v) of borneol was reported to decrease the number of TNF-α positive cells, and leukocyte infiltration in the brains of rats.…”
Section: P-cymene (8) Is a Naturally Occurring Aromatic Organic Compomentioning
confidence: 99%
“…F., effectively improves neurological deficits 24 h after forebrain ischemia. The beneficial effects of Borneol involve the reduction of leukocyte infiltration and ICAM-1 expression in the ischemic area [ 37 ].…”
Section: Tcm-mediated Suppression Of Leukocyte Infiltrationmentioning
confidence: 99%